(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
The current study investigates the impact of the Saudi Aramco Research Science Initiative (SA-RSI) on the participating gifted and talented Saudi female students’ acquisition of higher-order thinking skills. In this investigation, a particular emphasis is placed on the students’ metacognitive skills, time-management skills, problem-solving skills and decision-making skills. This study also measures the participants’ ability to engage in metacognitive thinking in terms of planning, self-monitoring and self-assessment. A scale was applied while measuring the students’ acquisition of skills in time management, problem solving and decision-making. The researchers employed multiple training methods and strategies in order to stimulate and enhance the participants’ abilities, especially in the areas of metacognitive thinking, problem solving, decision-making and time management. The study data indicate significant pre and post differences at the level of significance of 0.01 in the participants’ mean scores pertaining to meta-cognitive thinking skills, problem-solving skills, decision-making skills and time-management skills. Section one